Great expectations? Assessing the creation of national police organisations in Scotland and the Netherlands. (June 2019) - Terpstra, Jan; Fyfe, Nick R.
Against a background of recent structural reforms to police organisations in northern and western Europe, this paper examines the experiences of Scotland and the Netherlands where national police forces were established in 2013. Taking a comparative perspective, an analysis of the police reform proposals is followed by a review of the arguments for reform, the challenges of implementation and the findings emerging from the evaluations of the police reforms in each country. The paper concludes by drawing out the contrast between the 'great expectations' of the two police reforms articulated by the governments and the realities of bringing about rapid and large-scale organisational change, arguing that institutionalist perspectives on police reform have much to offer in making sense of the challenges of the police reform process.